Facility Layout Redesign for Tire Vulcanization SMEs Using Systemic Layout Planning and Graphical Methods (Case Study: IKM Tirta Kencana) - Wahyu Prayoga; Fitra Fitra; Reyhan Januasril Putra Pratama; Rama Sariantika (JTI: Jurnal Teknik Industri, 2025)
This study aims to redesign the layout of facilities at Tirta Kencana Ban Vulkanisir SME to improve production efficiency. The initial layout had problems in the form of unclear workstation boundaries, which caused workflow disruptions, inefficient operator movements, and the risk of musculoskeletal problems. To overcome these problems, this study applied and compared two methods, namely Systematic Layout Planning (SLP) and the Graphic Method. The research gap was addressed by focusing on the application of SLP in the tire vulcanizing SME sector, which has been rarely studied. The analysis was conducted in several stages, namely data collection, evaluation of the initial layout, and mapping of material movements using the Activity Relationship Diagram (ARD) and From-To Chart (FTC). The dual-method comparison showed that the Graphic Method was the most effective, reducing the total initial material movement distance from 421.5 meters to 349.3 meters, or a reduction of 15.73%. In addition, this new layout improves production flow, space utilization efficiency, and provides practical contributions in the form of reducing unnecessary operator movement, supporting improved ergonomics in the workplace, and minimizing the risk of musculoskeletal problems. Thus, redesigning the layout using the Graphic Method is a strategic solution to improve the operational efficiency and productivity of IKM Tirta Kencana Ban Vulkanisir. Keywords: Layout, Systematic Layout Planning, Tire Vulcanization